Evaluating the Performance of Sustainable Village Forest Management in Fakfak Regency Using MDS (Multidimensional Scaling) - Woretma, Mutmainah; Suharjito, Didik; Setiawan, Yudi (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
The social forestry program aims to provide access to community-based forest management. One of the social forestry schemes is the Village Forest. Fakfak Regency has 15 village forests that have received management licenses since 2018. However, there are various management obstacles. This research was conducted to analyze the sustainability status of 15 village forests in Fakfak Regency, to formulate appropriate management strategies. This study employed RapPForest analysis with the MDS (Multidimensional Scaling) method to evaluate the sustainability status of three dimensions and 22 attributes. Based on the analysis results, the ecological dimension has a very sustainable value (73.14), the economic dimension has a moderately sustainable status (50.01), and the social dimension is on a less sustainable index (45.79). In the ecological dimension, there are five village forests with a highly sustainable status; in the economic dimension, there are six village forests with a fairly sustainable status; in the social dimension, there are three village forests with a fairly sustainable status. The conclusion of this research is to develop recommendations for village forest management strategies that focus on achieving goals from the ecological, economic, and social dimensions.